Synthesis, computational quantum chemical study, in silico ADMET and molecular docking analysis, in vitro biological evaluation of a novel sulfur heterocyclic thiophene derivative containing 1, 2, 3-triazole and pyridine moieties as a potential human topoisomerase IIα inhibiting anticancer agent. (April 2019) - Murugavel, S.; Ravikumar, C.; Jaabil, G.; Alagusundaram, Ponnuswamy
Graphical abstract: Highlights: Synthesis of novel sulfur heterocyclic thiophene derivative (BTPT) is reported. Structure of BTPT is established by Single crystal XRD, supported by 1 H NMR, 13 C NMR, FTIR, UV–vis techniques. Computational quantum chemical investigations, in silico pharmacological and molecular docking studies were performed. MTT assay cytotoxicity results suggest, BTPT could be as effective anticancer drug. Abstract: Computational quantum chemical study and biological evaluation of a synthesized novel sulfur heterocyclic thiophene derivative containing 1, 2, 3-triazole and pyridine moieties namely BTPT [2-(1-benzyl-5-methyl-1H-1, 2, 3-triazol-4-yl)-6-methoxy-4-(thiophen-2-yl) pyridine] was presented in this study. The crystal structure was determined by SCXRD method. For the title compound BTPT, spectroscopic characterization like 1 H NMR, 13 C NMR, FTIR, UV–vis were carried out theoretically by computational DFT method and compared with experimental data. Druglikeness parameters of BTPT were found through in silico pharmacological ADMET properties estimation. The molecular docking investigation was performed with human topoisomerase IIα (PDB ID:1ZXM) targeting ATP binding site. In vitro cytotoxicity activity of BTPT/doxorubicin were examined by MTT assay procedure against three human cancer cell lines A549, PC-3, MDAMB-231 with IC50 values of 0.68/0.70, 1.03/0.77 and 0.88/0.98 μM, respectively. Our title compound BTPT reveals notable cytotoxicity against breast cancer cell (MDAMB-231), moderate activity with human lung cancer cell (A-549) and less inhibition with human prostate cancer cell (PC-3) compared to familiar cancer medicine doxorubicin. From the results, BTPT could be observed as a potential candidate for novel anticancer drug development process.